PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) TERHADAP MOTIVASI SISWAÂ MENGIKUTI PEMBELAJARAN BOLAVOLI DI KELAS X SMAN 1 PANGGUL KABUPATEN TRENGGALEK - RISKI NUGROHO, DIAN (Jurnal Pendidikan Olahraga dan Kesehatan, 2013)
Abstract Education is conscious effort and plan to create an atmosphere of learning and the process of learning so that learners are actively developing potential for her to have a religious, spiritual power of self-control, personality, intelligence, morals, as well as the necessary skills themselves, society and nation. By learning use the model of cooperative type TGT expected to increase the motivation of learning. This research aimed at described the application of a model of learning cooperative type tgt against motivation learn a student X SMAN 1 Panggul Kabupaten Trenggalek in learning bolavoli. This is the kind of research Quasi Experimental Design. Method of collecting data uses the method poll and observation. The population of research is all the students class X SMAN 1 Panggul Kabupaten Trenggalek the academic year 2012 / 2013. Based on the learning to use uji-t one party can be inferred that the average study result of the students experiment higher class than a student control. Response most students against a model of learning cooperative type tgt show category agree. Keywords : Cooperative Learning Model Type TGT, student learning Motivation, Volleyball Game.